Índice de masa corporal como factor pronóstico de mortalidad en pacientes con insuficiencia cardiaca - Burgos Granda, Jean Piere Aaron (2018)
Obesity is an independent risk factor to develop heart failure, however in recent years multiple scientific publications show the paradoxical relationship between obesity and mortality in patients with cardiovascular diseases. Objective: To establish the association of body mass index and mortality in patients with heart failure. Materials and Methods: Analytical, transversal and retrospective study of type cases and controls. We collected data from Clinical Histories of hospitalized patients diagnosed with heart failure in the cardiology service of the Teaching Regional Hospital of Trujillo during the period 2005-2015, from which a sample of 200 clinical histories distributed in 50 cases and 150 was selected. controls. Results: The average BMI was 27.01 and the highest frequency of mortality within the first three years of the diagnosis of HF was found in the normal weight category. No statistical association was found between the mortality in patients with HF and the intervening variables. Conclusion: The high body mass index is a protective factor against mortality within the first three years of the diagnosis of heart failure